Immunotropic effects of Curcuma longa extract as a component of original rectal suppositories in the dynamics of experimental Сrohn’s disease - М. V. Osikov; Е. V. Simonyan; A. E. Bakeeva; O. I. Ogneva (Медицинская иммунология)
Crohn’s disease is an urgent problem of modern gastroenterology due to increasing prevalence, severity of complications and side effects of the basic therapy, in particular upon treatment with 5-aminosalicylic acid (5-ASA). Searching, development and trials of new effective drugs with minimal side effects in Crohn’s disease is an urgent task. Curcuma longa is one of the initial substances containing curcumin with antioxidant, cytoprotective, anti-inflammatory properties. Its effectiveness has been demonstrated in few studies with its systemic use in Crohn’s disease treatment. Our aim was to perform a comparative analysis of curcumin and 5-ASA effect applied as a composition of rectal suppositories, studying clinical signs and indices of immune status in experimental Crohn’s disease. The study was performed on 70 Wistar male rats. Crohn’s disease was modeled by introduction of a 50% alcohol solution of trinitrobenzene sulfonic acid (TNBS) per rectum, and verified by clinical and morphological methods. Rectal suppositories, each containing 50 mg of 5-ASA and original suppositories containing 0.075 mg of curcumin were used over 12 hours during 7 days. The studies were performed on the 3rd , 5th and 7th days of Crohn’s disease.In the course of experimental TNBS-induced Crohn’s disease in animals, an increased frequency of bowel motility, appearance of blood in the stool, decreased body weight progressed from the 3rd to the 7th days of observation, along with increased number in CD3+, CD45RA+ lymphocytes in blood, higher number of segmented neutrophils, lower absorption and NBT-reducing activity of blood neutrophils, increased serum concentrations of IL-23, IgM, IgG. Composition of the new medication form was justified; production technology and standardization of the suppositories containing curcumin for the treatment for Crohn’s disease were developed. Usage of rectal suppositories with curcumin is associated with decreased severity of clinical signs, decrease and partial restoration of segmented neutrophils, CD3+ lymphocyte numbers in blood, recovery of absorption and NBT-reducing ability of blood neutrophils, and decrease of IL-23, IgM, IgG concentrations in serum. The effectiveness of rectal suppositories with curcumin is compared to the effectiveness of the use of rectal suppositories with 5-ASA in terms of disease activity index, the number of neutrophils and CD3+ lymphocytes in the blood, serum concentrations of IL-23, IgM and IgG, in, at lesser extent, in terms of absorption and NBT- reducing ability of blood neutrophils.The composition and production technology of rectal suppositories with curcuminwas developed; the leukocyte populations, CD3+, CD45RA+ lymphocytesin blood were assesed, neutrophil absorption and NBT-reducing ability, IL-23, IgM and IgG concentrations were determined; the use of rectal suppositories with curcumin in experimental Crohn’s disease is comparable with the effectiveness of rectal suppositories with 5-ASA.